2016
DOI: 10.1111/aji.12523
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for participation of neutrophil gelatinase‐associated lipocalin/matrix metalloproteinase‐9 (NGALMMP‐9) complex in the inflammatory response to infection in pregnancies complicated by preterm birth

Abstract: Background Neutrophil gelatinase-associated lipocalin (NGAL) is expressed in neutrophils and involved in innate immunity by sequestering iron. NGAL's ability to complex with matrix metalloproteinase-9 (MMP-9) and extend its gelatinolytic activity led us to investigate its role in pregnancies complicated by preterm birth (PTB) and intra-amniotic infection/inflammation (IAI). Methods We assayed the amniotic fluid (AF) levels of NGAL and MMP-9 in 308 women that had a clinically indicated amniocentesis and a nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Although lipocalin-2 has not yet been well evaluated in CVF in relation to MIAC/intraamniotic inflammation during pregnancy, lipocalin-2 is present in the vagina of healthy reproductive-age women, and its vaginal level is increased in women with vulvovaginal candidiasis [29]. A recent study on AF has shown that lipocalin-2 levels were elevated in AF with infection/inflammation [30], consistent with our results using CVF specimens.…”
Section: Discussionsupporting
confidence: 91%
“…Although lipocalin-2 has not yet been well evaluated in CVF in relation to MIAC/intraamniotic inflammation during pregnancy, lipocalin-2 is present in the vagina of healthy reproductive-age women, and its vaginal level is increased in women with vulvovaginal candidiasis [29]. A recent study on AF has shown that lipocalin-2 levels were elevated in AF with infection/inflammation [30], consistent with our results using CVF specimens.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, lipocalin-2 has been recently characterized as an adipose-derived cytokine, contributing to a low-grade inflammatory state in obese individuals 37 . In line with the known biology and function of lipocalin-2, AF levels of this protein have been reported as increased in pregnancies complicated by MIAC/histologic chorioamnioitis, IAI and preterm birth 38,39 . These results are in agreement with those of the present study.…”
Section: Discussionmentioning
confidence: 67%
“…For instance, MMP9 plays an important role in neutrophil migration across the endothelial barrier into tissues, which has implications in bullous pemphigoid or other skin diseases (39,63,64). Also, MMP9 can be secreted to form a complex with LCN2, and this MMP9-neutrophil gelatinase-associated lipocalin complex has been associated with cancer metastasis and inflammation (65,66). Furthermore, S100A9 protein in exosomes from chronic lymphocytic leukemia cells promotes NF-kB activity and disease progression (67), and exosomes showing common and unique proteins.…”
Section: Discussionmentioning
confidence: 99%